Assessment of Salivary and GCF pH in Periodontally Healthy and Stage II, Grade B Periodontitis Subjects: An In-vivo Study - Priyanka Zerwal; Vishakha Patil; Vidya Dodwad; Pooja Pharne; Allen Naorem; Niket Bhatt (Journal of Clinical and Diagnostic Research, 2025)
Introduction: Oral fluids can be used for the diagnosis of periodontal disease, as they can be easily collected. Saliva is a complex fluid that impacts oral health. Gingival Crevicular Fluid (GCF) is a physiological fluid as well as an inflammatory exudate present in the dentogingival space. It is established that every inflammatory change, along with resultant damage to tissues, leads to altered pH values of these fluids. Periodontal disease is a chronic inflammatory and infectious condition that affects the pH levels of saliva. Furthermore, it is understood that periodontal pathogens grow at acidic pH levels and the growth of these bacteria further contributes to changes in pH levels. Aim: To assess and compare the pH values of saliva and GCF in periodontally healthy subjects and those with chronic periodontitis. Materials and Methods: This in-vivo study was carried out at Outpatient Department of Periodontology, Bharati Vidyapeeth (Deemed To Be) University Dental College and Hospital, Pune, Maharashtra, India, over a period of three months, from August 2024 to October 2024. A total of 30 subjects visiting the department of periodontology underwent detailed periodontal examinations and were categorised into two groups: healthy periodontium (Group I, n=15) and generalised stage II, grade B periodontitis (Group II, n=15). Saliva and GCF samples were collected and analysed for pH levels. An independent sample t-test was applied. The analysis was conducted using Statistical Package for the Social Sciences (SPSS) version 25.0. A p-value of less than 0.05 was considered statistically significant. Results: A total of 30 subjects were studied, of which 20 were females and 10 were males, with a mean age of 32.5 years. In periodontally healthy subjects (Group I), the mean salivary pH was found to be 7.05±0.01, whereas, in stage II, grade B periodontitis subjects (Group II), the mean salivary pH was 6.14±0.60 (p=0.038). The mean GCF pH was 6.73±0.14 in Group I and 8.19±0.29 in Group II (p=0.041). Thus, in chronic periodontitis patients, the salivary pH was acidic and the GCF pH was alkaline compared to periodontally healthy subjects. Conclusion: The present study indicates that subjects with Stage II, Grade B periodontitis have an acidic salivary pH and a more alkaline GCF pH compared to periodontally healthy subjects.